PRODUCT INNOVATION STRATEGY IN IMPROVING CUSTOMER SATISFACTION IN COLD DRINK MSMEs - Putri, Triwulandari Nehru (Laboratorium Riset Ekonomi, 2024)
Beverage industry cold MSMEs facing challenge big in response change preference fast consumers and increasing competition tight. Product innovation is the key to increasing satisfaction and loyalty customers, but Many MSMEs are limited in implementing effective innovation strategies. This study aims to identify relevant product innovation strategies. for beverage SMEs cold and analytical its impact on satisfaction customers. The method used is a qualitative approach with interviews deep to owners and managers of MSMEs, as well as secondary data analysis from the case study. The results of the study show that innovation strategies such as surveys customers, social media monitoring, additions Variant’s products, and scale trials small effective in improving satisfaction customers. However, limited capital is a challenge the main thing in implementing the strategy. The implications of this research indicate importance deep understanding of preferences​ customers and the need to adapt quickly to market trends to support the sustainability of MSMEs. This research contributes for the development of more efficient marketing strategies and product innovation for MSMEs in the sector drink cold.